Public Perception of Circular Economy Implementation in Household Waste Management - Lizabeth sari dewi; ABD Haris; Nita Priska Ambarita; Muhammad Hirsan Hanafi (PT. Hafasy Dwi Nawasena, 2024)
Household waste production continues to increase with population growth, urbanization and consumptive lifestyles, contributing significantly to total global waste. This trend indicates not only an increase in the quantity of waste, but also the complexity of its management, especially in urban areas. The circular economy concept offers a sustainable solution by utilizing the principles of recycling, waste reduction, and resource reutilization. This research explores the community's perception towards the application of circular economy in household waste management through descriptive qualitative method. The results showed that most communities understand the basic principles of circular economy, but the implementation of this practice is still constrained by the lack of education and supporting infrastructure. High environmental awareness is proven to contribute to the active participation of the community, while limited resources in rural areas hinder the equitable implementation of this concept. Collaboration between the government, private sector and communities is needed to improve infrastructure and provide sustainable education programs. This study confirms that the paradigm transformation of circular economy-based waste management is not only able to reduce the environmental burden, but also create new sustainable economic opportunities. The results of the study are expected to serve as a basis for policy development that supports the implementation of circular economy more widely and effectively.